Penerapan Model Discovery learning berbantuan Teka-teki Silang pada Mata Pelajaran IPA - Muflihatin, Laili; Sunarti, Titin; Tarmuji, Tarmuji (STKIP HARAPAN BIMA, 2024)
This study aims to determine the results of applying the Discovery learning model assisted by crossword puzzles applied to science subjects on student learning outcomes. This research was carried out at SMPN 58 Surabaya on class VIII H students with the main material being sound waves during the even semester of the 2023/2024 academic year. The type of research method used is classroom action research (CAR). Classroom action research is carried out in two cycles, which has four stages in each cycle, namely planning, implementation, observation and reflection. The instruments used are observation sheets, learning result test sheets and questionnaires. Data collection techniques used include observation, tests and documentation and the analysis technique used in this research is descriptive analysis. Based on the research results, an increase in learning outcomes was obtained as seen from the learning activities and learning completion of students with percentages in cycle 1 respectively 65% and 74%, and in cycle II obtained respectively 90% and 93%. Thus, the use of the Discovery learning model assisted by crossword puzzles can improve student learning outcomes well.